KAJIAN JARAK TANAM DAN FREKUENSI PENYEMPROTAN PUPUK CAIR TERHADAP PERTUMBUHAN DAN PRODUKSI KACANG HIJAU (Phaseolus radiatus L.) - Mariyatul Qibtiyah (Agriculture faculty, Darul ‘Ulum Islamic University (UNISDA) of Lamongan, 2017)
To increase the maximum green beans production strongly depends from the available land area, technology and systems of cultivation. One of the system or the way it is with the application of cultivation planting distance and frequency of spraying. This research was carried out in the village of Cungkup Sub-district Shoots lamongan. Located at an altitude of place ± 8 meters above sea level. This study used a Randomized Design Group (RAK) factorial. Factor 1: trunks (J) 20 cm x 10 cm, 30 cm and 40 cm x 20 cm x 10 cm. 2 Factors: the frequency of spraying (F) 6 x, 8 x and 10 x spraying. The conclusion that the combination of the best treatment at planting distance 30 cm x 20 cm and spraying frequency 8 x (J2F2).